A Study on the production system of Norca Rubber Company - Bajet, Leah Rosario L.; Fajardo, Conrad Robert M.; Frianeza, Wilfredo S.; Gutierrez, Egbert Peter G.; Sison, Reuben R.; Villamin, Reynaldo V. (College of Engineering, 1983)
This is a study of the production system of Norca Rubber Company. The company produces engineering products made of Adiprene ( a type of urethane rubber) and its style of production is job-shop. Adiprene is a new material made in North America and its use in engineering products is not yet widely known. This is why the marker of these products is small but growing. Norca Rubber company is the sole manufacturer of these products in the country. It does not market the product itself, but rather, it sells them to a sister company, the Regina Trading Company, which resells the Adiprene products to its customers. In studying the production system, certain problems, current and potential, of the systems components surfaced. it is a purpose of this project to identify, analyze, and recommend solutions to these problems. In analyzing the problems and their probable causes, it was found necessary to extend the study outside the system if solutions to them were arrived at. The most glaring problem, which was cited to us by the company, is the need for the design of a new inventory system in anticipation of the inevitable cutoff of raw material supply from their local raw material supplier. When the company starts to order its raw materials direct from the manufacturers in North America, lead time, which is the time elapsed between placing the order and receiving it, will play an important role in the determination of the inventory policy. This is an inventory problem but not only one. It was found out that the inventory would not lend itself to any solution unless demand for the products was known or at least could be determined by some intelligent or methodical guessing- a forecasting problem. However, it was found out that forecasting was a problem because the market for the product was so erratic that there was no way to know or guess the future demand. And so, the behaviour of the market made any design for production planning, especially inventory, unworkable. It was realized, however, that the behaviour of the market could be made more orderly and more predictable and this could be done by the trading company itself. Once a plan for accomplishing this had been designed, the construction of solution models for the rest of the problem - problems in the proper production was commenced. Certain problems were also encountered in the layout of the manufacturing plant, primarily due to its newness and the nature of job-shop production. Improvements in this area were also discussed.